2016
DOI: 10.1002/adma.201506232
|View full text |Cite
|
Sign up to set email alerts
|

One‐Shot Immunomodulatory Nanodiamond Agents for Cancer Immunotherapy

Abstract: The use of functional nanodiamonds (fNDs) to deliver CpG oligonucleotides (ODNs) for sustained immunostimulation is reported. It is demonstrated that monotherapy using this immunostimulatory agent significantly suppresses the tumor growth in two murine tumor models. This fND-based nanoagent opens new opportunities for immunotherapy, as well as clinical applications of various types of therapeutic nucleic acids.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
81
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(82 citation statements)
references
References 53 publications
1
81
0
Order By: Relevance
“…Among a wide variety of nanomaterials-based vehicles, nanodiamonds (NDs) have shown outstanding delivery ability and excellent biocompatibility (Zhang et al, 2016). Zhao et al have demonstrated that detonation nanodiamond with hyperbranched polyglycerol coating (dND-PG) loaded with anticancer drug and led by efficient targeting moiety can realize highly preferential toxicity to the intended tumor cells through specific uptake mechanisms, while with minimum uptake and toxicity in macrophages (Zhao et al, 2014).…”
Section: Nanodiamondmentioning
confidence: 99%
“…Among a wide variety of nanomaterials-based vehicles, nanodiamonds (NDs) have shown outstanding delivery ability and excellent biocompatibility (Zhang et al, 2016). Zhao et al have demonstrated that detonation nanodiamond with hyperbranched polyglycerol coating (dND-PG) loaded with anticancer drug and led by efficient targeting moiety can realize highly preferential toxicity to the intended tumor cells through specific uptake mechanisms, while with minimum uptake and toxicity in macrophages (Zhao et al, 2014).…”
Section: Nanodiamondmentioning
confidence: 99%
“…The CpG ODNs, generally present in bacterial and viral DNA, can be recognized by mammalian immune system through Toll‐like receptor 9 (TLR9) and promote the secretion of a series of proinflammatory cytokines . Although the use of CpG ODNs has been proved an enhancement of immunity and various nanomaterials have been studied for delivering CpG ODNs into target cells, yet the costly materials, the lengthy fabrication processes, and the inability to deliver the CpG ODNs together with antigens into the same cells by using these delivery vehicles hamper their further application. The OVA@ZIF‐8‐CpG nanoparticles could be synthesized easily and economicly.…”
Section: Introductionmentioning
confidence: 99%
“…Nanomaterials are defined as materials with sizes ranging from 1 to 1000 nm in at least 1D. Due to the unique physicochemical properties such as higher surface area‐to‐volume ratio and enhanced permeability and retention (EPR) effect, they have presented promising application potential in diagnosis and therapy for various kinds of diseases . On the other hand, these properties possessed by nanomaterials are not always helpful, accumulating evidences indicate that the nanosized crystals could induce much greater toxicity than similar bulk materials and even affect the cell death mode .…”
Section: Introductionmentioning
confidence: 99%